Design and simulation of 10 MHz MEMS oscillator - Taufik, Mohamad Syamsi; Khan, Sheroz; Nordin, Anis Nurashikin; Zainuddin, Ahmad Anwar (IEEE, 2014)
Design and analysis of a 10MHz oscillator is presented. To perform oscillator circuit simulations, the CMOS-MEMS Clamped-Clamped beam) resonator structure is modeled using its RLC equivalent circuit approach. For a MEMS resonator to be able to function as an oscillator it needs to be coupled with an amplifier circuit. The OP AMP achieves a gain of 1.8 V and VSS of -1.8 V. The two-stage CMOS OP AMP is combined with 10MHz CC-beam resonator to create and oscillator at the frequency of ~10MHz with loop gain of 16 dB.The oscillator is simulated using Cadence Design Systems.